2017
DOI: 10.1115/1.4038161
|View full text |Cite
|
Sign up to set email alerts
|

Large Eddy Simulation Study on Forced Convection Heat Transfer to Water at Supercritical Pressure in a Trapezoid Annulus

Abstract: It is now well known that heat transfer to fluid at supercritical pressure in a confined channel shows complex behaviors. This is due to the strong variations of the thermal–physical properties resulting from the changes of pressure and temperature. To improve the reliability and efficiency of the supercritical water-cooled reactors (SCWRs) to be designed, the understanding of supercritical fluid flow in the fuel assemblies is very important. The study reported here reconsiders a simplified geometry made of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…Salamana and El-Morshedy [7] simulated buckled flow in a geometry akin to that used Davari et al [6]. [13] and Mohd amin et al [14] has shown the strouhal number of this flow structure is geometry dependant even in the event of strong buoyancy influence [13] and strong property variation [14]. Chang and Touvelaris [15,16]…”
Section: Introductionmentioning
confidence: 99%
“…Salamana and El-Morshedy [7] simulated buckled flow in a geometry akin to that used Davari et al [6]. [13] and Mohd amin et al [14] has shown the strouhal number of this flow structure is geometry dependant even in the event of strong buoyancy influence [13] and strong property variation [14]. Chang and Touvelaris [15,16]…”
Section: Introductionmentioning
confidence: 99%